2016
DOI: 10.13169/workorgalaboglob.10.2.0001
|View full text |Cite
|
Sign up to set email alerts
|

The precariousness of knowledge workers: hybridisation, self-employment and subjectification

Abstract: In knowledge-based industries, work is circumscribed by the cognitive frames of creativity in the representations of subjects, but simultaneously demands adaptability, in a context in which deregulation and individualisation are now normal. The ethics of self-activation are therefore inextricably intertwined with the demands of intensification, standardisation and self-commodification. The first volume of this Special Issue which is composed of two different parts is focused on the phenomena of hybridisation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…Among non-standard employment relations, the so-called "solo self-employment"-self-employed workers without employees or "own account workers"-is increasingly intertwined with precarious forms of work, in which individuals have low legal protection, a limited coverage in terms of social security provisions, little capacity for savings, insurance or pensions, and are hardly included in traditional interest representation (Stanworth and Stanworth, 1995;Schulze Buschoff and Schmidt, 2009;Dekker, 2010;Keune, 2013;Spasova et al, 2017;Jansen and Sluiter, 2019). On top on this, solo self-employment is a category that is challenging our understanding of the nature of employment relationship, that is to say the opposition between employers and employees, and is also encouraging discussion around the emergence of "hybrid" areas of work (Murgia et al, 2016;Armano and Murgia, 2017;Murgia and Pulignano, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among non-standard employment relations, the so-called "solo self-employment"-self-employed workers without employees or "own account workers"-is increasingly intertwined with precarious forms of work, in which individuals have low legal protection, a limited coverage in terms of social security provisions, little capacity for savings, insurance or pensions, and are hardly included in traditional interest representation (Stanworth and Stanworth, 1995;Schulze Buschoff and Schmidt, 2009;Dekker, 2010;Keune, 2013;Spasova et al, 2017;Jansen and Sluiter, 2019). On top on this, solo self-employment is a category that is challenging our understanding of the nature of employment relationship, that is to say the opposition between employers and employees, and is also encouraging discussion around the emergence of "hybrid" areas of work (Murgia et al, 2016;Armano and Murgia, 2017;Murgia and Pulignano, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging professionals (Maestripieri & Cucca, 2018) have assumed the market logic as naturally constituting their essence while not perceiving the insecurity determined by exposure to the market as problematic in an era of hegemonic neoliberalism (Murgia, Maestripieri & Armano, 2016). As a natural consequence, less power implies a weaker association between professional status, social status, and financial rewards (Bellini & Maestripieri, 2018, p. 7).…”
Section: The Changing Nature Of Professions and The Role Of New Workpacesmentioning
confidence: 99%
“…The traditional understanding of the term knowledge worker (KW) is characterized by the following distinctions: erudition; excellent education (Kowalski, 2011); ability to provide CENTRAL EUROPEAN BUSINESS REVIEW expert opinions (Wellin, 2013); professionalism and a closed catalogue of professionsdoctor, lawyer, architect (Drucker, 2011;Jashapara, 2014;Kowalski, 2011;Wellin, 2013); autonomy -autonomous participation in knowledge processes, free professions (Drucker, 2011;Jashapara, 2014;Kowalski, 2011;Wellin, 201), professional ethos and moral responsibility (Chong, Ismail, Thi, and Kanafani, 2017;Harlow, 2018;Murgia, Maestripieri, and Armano, 2016). The characteristics of the KW concept eventually evolved in accordance with the words of Drucker (2011, p.132-133): "Knowledge workers today are productively used in some organizations (...) business entities and state administration.".…”
Section: Literature Review and Hypotheses Development 1knowledge Wormentioning
confidence: 99%
“…However, innovativeness and cognitive tendencies in an employee's profile have an impact on innovation and efficiency (Lewis, Agarwal, and Sambamurthy, 2003). On the basis of the above, it can be concluded that the most important characteristics of KW include: ethics (Chong et al, 2017;Evans, 2005;Griffin, 2017;Murgia et al, 2016;Steinmann and Schreyogg, 2001;Tidd, and Bessant, 2013), autonomy (Janz, Colquitt, and Noe,1997;Jungert, Koestner, Houlfort, and Schattke, 2013), cooperation (Davenport, 2007, Jashapara, 2014Tidd, and Bessant, 2013), professionalism (Frick, 2010;Owen, 2013;Tidd, and Bessant, 2013), intellectualism (Hwang, Kettinger, and Yi, 2015), innovativeness (Fischer, Malycha, and Schafmann, 2019;Tidd, and Bessant, 2013), and reputation (Bhatnagar, Gupta, Alonge, and George, 2017;Frick, 2010;Hwang et al, 2015), as shown in Figure 1. At the same time, it is important to define the concept of the level of absorption of the KW's characteristics.…”
Section: Literature Review and Hypotheses Development 1knowledge Wormentioning
confidence: 99%